Response to comments on “Evolutionary transitions between beneficial and phytopathogenic Rhodococcus challenge disease management” - Chang, Jeff H; Putnam, Melodie L; Grünwald, Niklaus J; Savory, Elizabeth A; Fuller, Skylar L; Weisberg, Alexandra J (eLife, 2018)
Randall et al., 2018 and Vereecke, 2018 have raised concerns about a paper we published (Savory et al., 2017). Here, we respond to those concerns.
Keywords: Rhodoococcus; pistachio bushy top syndrome; diagnosis; R. fascians